2022
DOI: 10.3389/fphar.2022.825842
|View full text |Cite
|
Sign up to set email alerts
|

Crocins for Ischemic Stroke: A Review of Current Evidence

Abstract: Crocins (CRs) and the related active constituents derived from Crocus sativus L. (Saffron) have demonstrated protective effects against cerebral ischemia and ischemic stroke, with various bioactivities including neuroprotection, anti-neuroinflammation, antioxidant, and cardiovascular protection. Among CRs, crocin (CR) has been shown to act on multiple mechanisms and signaling pathways involved in ischemic stroke, including mitochondrial apoptosis, nuclear factor kappa light chain enhancer of B cells pathway, S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 249 publications
(301 reference statements)
0
3
0
Order By: Relevance
“…Furthermore, Crocin has been reported to enhance the memory abilities of aging Wistar rats by exerting its antioxidant activities (Heidari et al., 2017 ). Although few studies definitively state whether Crocin can cross the blood‐brain barrier, several studies have demonstrated that Crocetin can cross the blood‐brain barrier (Shahbaz et al., 2022 ). In addition, Zhang et al.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, Crocin has been reported to enhance the memory abilities of aging Wistar rats by exerting its antioxidant activities (Heidari et al., 2017 ). Although few studies definitively state whether Crocin can cross the blood‐brain barrier, several studies have demonstrated that Crocetin can cross the blood‐brain barrier (Shahbaz et al., 2022 ). In addition, Zhang et al.…”
Section: Discussionmentioning
confidence: 99%
“…Although few studies definitively state whether Crocin can cross the blood-brain barrier, several studies have demonstrated that Crocetin can cross the blood-brain barrier (Shahbaz et al, 2022). In addition, Zhang et al (2017) have reported that Crocin may protect against cerebral ischemia in elderly patients by maintaining the integrity of the blood-brain barrier.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, crocin is found to restore striatal dopamine levels, reduce α‐synuclein levels and dopaminergic neuron degeneration along with improvement of motor functions in PD mouse and rat models (Haeri et al, 2019; Rao et al, 2019; Salama et al, 2020). However, the therapeutic yields of crocin are reported to be restrained by its poor bioavailability and BBB permeability (Rahaiee et al, 2017; Shahbaz et al, 2022). Celastrol , the most abundant compound of the roots of Tripterygium wilfordii is reported to possess low aqueous solubility and bioavailability, as well as exerts toxicities in the heart, liver and kidney at higher doses (Fang & Tang, 2020; Shi et al, 2020).…”
Section: Phyto‐compounds and Their Neuroprotective Effects In Ad And ...mentioning
confidence: 99%